2021
DOI: 10.3390/agronomy11020403
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiology, Productivity and Quality of Soybean (Glycine max (L.) Merr.) cv. Merlin in Response to Row Spacing and Seeding Systems

Abstract: The appropriate row spacing and sowing density of soybeans are the basic non-input and pro-environmental agrotechnical factors. The optimal spacing of plants in the field can be crucial in terms of reducing competition between plants for water, nutrients and light, which is particularly important for photosynthesis and maximizes the use of environmental resources. The field experiment was carried out in the years 2017–2019 at the Experimental Station for Cultivar Assessment in Przecław, Poland, on Merlin cv. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…It has been observed that the height of the first pod increases with the overall height of the plant as shown in figure 1. Anuradha et al (2014) [5] and Jańczak-Pieniążek et al (2021) [15] also reported a positive correlation between plant height and basal pod height. This increase is particularly noticeable under narrow spacing, while it decreases with greater spacing.…”
Section: First Pod Heightmentioning
confidence: 99%
“…It has been observed that the height of the first pod increases with the overall height of the plant as shown in figure 1. Anuradha et al (2014) [5] and Jańczak-Pieniążek et al (2021) [15] also reported a positive correlation between plant height and basal pod height. This increase is particularly noticeable under narrow spacing, while it decreases with greater spacing.…”
Section: First Pod Heightmentioning
confidence: 99%
“…Therefore, attempts to soybean cultivation in Polish conditions seems to be promising. One way to achieve protein balance stability is to improve legume yields and, in particular, to improve soybean agronomics in European countries 2 , 4 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Its also known as one of the most widely grown and traded crops worldwide (FAO, 2018). The area planted with soybeans in 2019 was 120.5 million ha, and the average yield was 2.77 (Jańczak-Pieniążek et al, 2021). Due to its chemical composition, the soybean is essential for both humans and animals.…”
Section: Introductionmentioning
confidence: 99%